Leaf Micromorphological characteristics of selected vatica spp. And comparison with other genera in tribe dipterocarpeae (dipterocarpaceae) - Miraadila, Mohd Isa (Universiti Malaysia Sarawak, UNIMAS, 2013)
The Asian Dipterocarpaceae family has been divided into two major groups; Tribe Shoreae and Dipterocarpeae based on the arrangement of sepals and number of chromosome. Species identification for certain genera within the tribe Dipterocarpeae are still doubtful due to lacked of information. Therefore, detail studies on morphology, micro morphology and anatomy of leaves for 10 selected Vatica species, Upuna borneensis and two Anisoptera species have been conducted. Examinations on the leaf morphological have been observed via naked eyes, lens, microscopes and Scanning Electron Microscopic. The results from leaf morphological observation show significant difference for both Meanwhile, the results from micromorphology studies showed significant difference only at generic level. The noticeable difference that spotted on the leaf surfaces were the presence of trichomes. The peltate and stellate trichomes were encountered in Vatica species while comparably, simple trichomes were observed only on U. borneensis and the two Anisoptera species. Moreover, anatomy studies which included the petiole tranverse section and epidermal characteristics showed no significant difference for both generic and species levels except for V. ryncocarpa. The results from morphology, micromorphology and anatomy studies were very useful for taxonomical aspects in Dipterocarps family. However, comprehensive studies should be conducted to achieve precise results.